Characterization of the reliability and uniformity of an anodization-free fabrication process for high-quality Nb/Al-AlOx/Nb Josephson junctions - Kempf, Sebastian; Ferring-Siebert, Anna; Fleischmann, Andreas; Gastaldo, Loredana; Enss, Christian (Superconductor science and technology, 2013)
We have developed a reliable and reproducible fabrication process for high-quality Nb/Al-AlOx/Nb Josephson junctions that completely avoids anodization techniques, that are typically used to define the junction area, to electrically insulate the base electrode as well as the sidewalls of the counter-electrode and to protect the tunnel barrier. Hence, this process is well suited for the fabrication of electrically floating junction-based devices such as non-hysteretic rf-SQUIDs. Josephson junctions of various sizes have been produced and characterized at 4.2 K. We found that our junctions have a high quality, which is confirmed by measured gap voltages Vg and Ic Rn products up to 2.9 and 1.8 mV and on-wafer average values of the resistance ratio Rsg/Rn above 30 in most cases. Here, Rsg and Rn denote the subgap and the normal state resistance of a Josephson junction. Although the uniformity of the properties of the Josephson junctions across a wafer is high, we observe some systematic variations of the critical current density and the gap voltage over an entire wafer. These variations are most likely to be attributed to residual stress in the Nb films as well as the surface roughness of the Nb base electrode.
Gesehen am 28.04.2021
Im Titel ist der griechische Buchstabe chi tiefgestellt